ANALYSING THE IMPACT OF RELIGIOUSITY TOWARDS EMPLOYEE’S WELFARE AT UNIVERSITY OF MUHAMMADIYAH MALANG - Suliswanto, Muhammad Sri Wahyudi; Muhajirin, Muhajirin; Yuli, Sri Budi Cantika; Abdullah, M. Faisyal (Universitas Muhammadiyah Malang, 2020)
Several research found that there is relationship between religious and economic spirit. This study intended to determine the relationship between religiosity towards employee's welfare at University of Muhammadiyah Malang. The method of this study is quantitatif using questionnaire as method of collecting data. The method of analysis data using Partial Least Square (PLS) with several valid variables. The result indicates that religiousity have significance impact on the welfare of employee of University of Muhammadiyah Malang.